Cities under siege - Bauche, Maurice D.; Westfall, Matthew (ADB, 1995)
Profiles innovative urban management efforts in New Delhi, India to cope with urban poverty; in Bangkok, Thailand to improve traffic management and in Manila in an emergent "clean and green" movement. Interviews with urban managers, technicians, elected local officials and development experts capture the trends and issues facing Asia's urban future.